Religiosity Representation in Sore Band's Song Lyrics Tatap Berkalam - Adhiksa Sasono, Yan; Gita Sukmono, Filosa (Jogjakarta Communication Conference (JCC), 2023)
This study examines the representation of religiosity in the lyrics of the song "Tatap Berkalam" by Sore Band. In this study, the qualitative method is interpretive with data analysis techniques using text analysis with a semiotic approach. Sources of data obtained from primary data directly from the object of research and secondary data from various supporting references. The music itself has many essential elements, such as arrangement, composition, instruments, and lyrics, which can represent a view of society. The song face to face also represents how one's life journey is to get closer to God. The result obtained is that religiosity in the song is described as a manifesto of life spoken by God Almighty.